Rearing of Rhipicephalus annulatus ticks on rabbits for the biological transmission of Anaplasma marginale - Sikandar Ali; Abdullah Saghir Ahmad; Kamran Ashraf; Jawaria Ali Khan; Muhammad Imran Rashid (Veterinary World, 2024)
Background and Aim: Anaplasma marginale is an obligate intraerythrocytic rickettsial parasite that infects cattle in tropical and subtropical regions. There is no evidence that A. marginale inoculation can be used to culture Rhipicephalus annulatus in rabbits. This study aimed to determine the molting of R. annulatus larvae, nymphs, and adults on rabbits as well as nymphs and adults of R. annulatus on calves with or without A. marginale. Transstadial, horizontal, and transovarial transmissions of A. marginale in R. annulatus reared on rabbits and calves were evaluated.